Genome-wide identification and expression analysis of the GASA gene family in Chinese cabbage (Brassica rapa L. ssp. pekinensis) - Bingxin Sun; Xianlei Zhao; Jiahui Gao; Jie Li; Yue Xin; Yonghui Zhao; Zhiyong Liu; Hui Feng; Chong Tan (BMC Genomics, 2023)
Abstract Background The Gibberellic Acid-Stimulated Arabidopsis (GASA) gene family is widely involved in the regulation of plant growth, development, and stress response. However, information on the GASA gene family has not been reported in Chinese cabbage (Brassica rapa L. ssp. pekinensis). Results Here, we conducted genome-wide identification and analysis of the GASA genes in Chinese cabbage. In total, 15 GASA genes were identified in the Chinese cabbage genome, and the physicochemical property, subcellular location, and tertiary structure of the corresponding GASA proteins were elucidated. Phylogenetic analysis, conserved motif, and gene structure showed that the GASA proteins were divided into three well-conserved subfamilies. Synteny analysis proposed that the expansion of the GASA genes was influenced mainly by whole-genome duplication (WGD) and transposed duplication (TRD) and that duplication gene pairs were under negative selection. Cis-acting elements of the GASA promoters were involved in plant development, hormonal and stress responses. Expression profile analysis showed that the GASA genes were widely expressed in different tissues of Chinese cabbage, but their expression patterns appeared to diverse. The qRT-PCR analysis of nine GASA genes confirmed that they responded to salt stress, heat stress, and hormonal triggers. Conclusions Overall, this study provides a theoretical basis for further exploring the important role of the GASA gene family in the functional genome of Chinese cabbage.